Expanding Microfinance in Brazil : Credit Utilization and Performance of Small Firms - Skoufias, Emmanuel; Leite, Phillippe; Narita, Renata (Taylor and Francis, 2013)
We take advantage of the natural experiment generated by the exogenous change in government policy towards microcredit to evaluate the impact of the increased supply of microcredit on the utilisation of credit by micro-entrepreneurs. Based on micro-entrepreneurs' survey and administrative data from a microcredit programme in Brazil, we show that: the increased supply of microcredit raised formal credit utilisation and this does not crowd out the use of informal credit sources; formal credit taking improves business performance; and returns are larger for women- than for men-owned firms, but males employ significantly more workers after taking formal credit than females.